2000
DOI: 10.1034/j.1399-3054.2000.108003300.x
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis, biomass partitioning and peroxisomicine A1 production of Karwinskia species in response to nitrogen supply

Abstract: Species of the genus Karwinskia are medicinal woody plants producing secondary metabolites (anthracenones, peroxisomicine A1) with antitumour effects. We investigated the photosynthetic and growth characteristics of Karwinskia parvifolia Zucc. and Karwinskia humboldtiana Rose plants grown at two rates of nitrogen supply. There were significant differences in growth, CO2 exchange (photosynthesis, respiration), chlorophyll and nitrogen concentration between plants grown at high nitrogen supply (HN) and low nitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
2
1
Order By: Relevance
“…The different composition and density of leaves may also explain the unexpected differences in the mass-specific expression of our results with E. angustifolium. In contrast to this study, several others found that the rates of photosynthesis and leaf respiration per leaf weight, specific leaf area and leaf mass ratio are higher in plants grown in high N soils (Field et al, 1983;Field and Mooney, 1983;Masarovicova et al, 2000;Poorter et al, 1995). Nevertheless, the difference in available nutrition did not significantly affect the rate of photosynthesis in this study.…”
Section: Environmental Effects On P Max Valuescontrasting
confidence: 99%
See 1 more Smart Citation
“…The different composition and density of leaves may also explain the unexpected differences in the mass-specific expression of our results with E. angustifolium. In contrast to this study, several others found that the rates of photosynthesis and leaf respiration per leaf weight, specific leaf area and leaf mass ratio are higher in plants grown in high N soils (Field et al, 1983;Field and Mooney, 1983;Masarovicova et al, 2000;Poorter et al, 1995). Nevertheless, the difference in available nutrition did not significantly affect the rate of photosynthesis in this study.…”
Section: Environmental Effects On P Max Valuescontrasting
confidence: 99%
“…Respiration accompanies the observable CO 2 exchange during daytimes. Therefore we fitted a Michaelis-Menten-type equation (Michaelis and Menten, 1913) for each set of our measurements as follows:…”
Section: Chamber Measurements Of Co 2 Exchangementioning
confidence: 99%
“…2 mg g 21 in oak-hornbeam forest. Lower chlorophyll content is probably due to lower nitrogen content in carnivorous plants than in noncarnivorous plants, because a positive correlation between chlorophyll and nitrogen content is generally found for plants (Masarovičová et al, 2000).…”
Section: Gas Exchange and Leaf Chemistrymentioning
confidence: 99%